NEUROMUSCULAR PARALYSIS BY A SINGLE INJECTION OF LINCOMYCIN - Shah, Syed Sajid Hussain; Saleem, Munaza; Mehood, Tahir (Journal of Ayub Medical College Abbottabad, 2014)
A seven years old girl presented with history of sudden onset of generalized body weakness to an extent that she was not able to move any body part. On thorough history it was revealed that she was given intramuscular injection lincomycin at private clinic which lead to neuromuscular paralysis of whole body. This antibiotic is currently not being used in humans and being only used as veterinary medication. Keywords: Neuromuscular paralysis, complication, antibiotic